Analisis Pembangunan Pasraman Sebagai Pembinaan Masyarakat Di Kecamatan Fena Leisela, Kabupaten Buru, Provinsi Maluku - Roni Waemese; I Made Sutresna; I Made Jaya Negara SP (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2022)
This research provides an overview of the necessity for developing pasraman as a vehicle for religious education, especially for young Hindu generation and the community in Fena Leisela Sub District, Buru District, of Maluku Province. The discussions in this research are: 1) How is the Public Perception espacially community in Fena Leisela Sub District about it; and 2) How is the real potential of Community for concern issues. The aim of this research is to ansure that Community in Fena Leisela Sub District can build Pasraman as a vehicle for educate the Community. In other word the developing of this pasraman is very important because there are still a lot of Hindu people in that region who do not understand the teachings of Hinduism. When the Pasraman can be build then the convertation will not heven in the Community. The theories used in this research are 1) Swot Analysis Theory, 2) Human Capital Improvement Theory, and 3) Development Theory. The method in this research is a description method, with the qualitative approach. Research data, especially primary data carried out by directly discussion in the field by with several Hindu religious figures or institutions and community leaders. On the contrary, the secondary data have got from some references to support the results of research. The results of concern research namely: Community have understood the benefits of establishing Pasraman in Fena Leisela Sub District; the Community have ability to develop the Pasraman; They also have ability to maintain pasraman security; Land for developing Pasraman have been ready; Availability of the Teacher candidates for Pasraman have fullfil the standar; Curriculum for Pasraman generally have been developed by the government and community should add the row material for specific identity value; Controler for Pasraman have been ready per-standart.